An Ex-Ante analysis of the distribution of benefits from technical change among classes of consumers and producers: the case of beans in Brazil - Pachico, Douglas H.; Jones, Peter G.; Lynam, John K. (International Center for Tropical Agriculture, 1984)
In Brazil, the world`s largest bean producer, the annual production value is over US$ billion. Beans contribute more to total national protein consumption than any other product, especially among the poor, who get over 30 percent dietary protein from beans. Available technological options for improving productivity through breeding are reviewed; a consumer surplus model, which disaggregates benefits among 4 consuming and 2 producing groups, was developed to estimate their potential impact. Gross annual social benefits are highest with scale-neutral technology, which leads to the greatest aggregate supply shift. Consumer benefits rise, going from small- farm biased toward scale- neutral technology but this is counterbalanced by a fall in benefits to small farmers. Although total social benefits are greater for large-farm than small-farm biased technology, the low- income target groups of poor consumers and small farmers are, in the aggregate, much less well off with large-farm biased technology. Costs are 50 percent higher when technology is biased toward small farmers, who face more stresses. Policymakers are faced with difficult equity vs. efficiency decisions. (CIAT)